BdCIPK31, a Calcineurin B-Like Protein-Interacting Protein Kinase, Regulates Plant Response to Drought and Salt Stress - Luo, Qingchen; Wei, Qiuhui; Wang, Ruibin; Zhang, Yang; Zhang, Fan; He, Yuan; Zhou, Shiyi; Feng, Jialu; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2017)
Calcineurin B-like protein interacting protein kinases (CIPKs) are vital elements in plant abiotic stress signaling pathways. However, the functional mechanism of CIPKs has not been understood clearly, especially in Brachypodium distachyon, a new monocot model plant. In this study, BdCIPK31, a CIPK gene from B. distachyon was characterized. BdCIPK31 was downregulated by polyethylene glycol, NaCl, H2O2, and abscisic acid (ABA) treatments. Transgenic tobacco plants overexpressing BdCIPK31 presented improved drought and salt tolerance, and displayed hypersensitive response to exogenous ABA. Further investigations revealed that BdCIPK31 functioned positively in ABA-mediated stomatal closure, and transgenic tobacco exhibited reduced water loss under dehydration conditions compared with the controls. BdCIPK31 also affected Na+/K+ homeostasis and root K+ loss, which contributed to maintain intracellular ion homeostasis under salt conditions. Moreover, the reactive oxygen species scavenging system and osmolyte accumulation were enhanced by BdCIPK31 overexpression, which were conducive for alleviating oxidative and osmotic damages. Additionally, overexpression of BdCIPK31 could elevate several stress-associated gene expressions under stress conditions. In conclusion, BdCIPK31 functions positively to drought and salt stress through ABA signaling pathway. Overexpressing BdCIPK31 functions in stomatal closure, ion homeostasis, ROS scavenging, osmolyte biosynthesis, and transcriptional regulation of stress-related genes.